2021
DOI: 10.1002/ecs2.3427
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐induced yellow‐cedar decline on the island archipelago of Haida Gwaii

Abstract: The global rise in temperature and associated changes in climate have led to decline of forests around the globe, across multiple species and ecosystems. Yellow-cedar (Callitropsis nootkatensis) decline is one of the most severe in North America. We found abundant evidence of tree decline and mortality on Haida Gwaii across multiple watersheds and over a range of elevations. This decline on Haida Gwaii parallels the broader yellow-cedar decline in terms of spatial distribution, symptoms, magnitude, and timing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 42 publications
2
13
1
Order By: Relevance
“…The sensitivity of yellow-cedar to warm dry winters in recent decades is consistent with other studies showing increased vulnerability to late-winter thaw-freeze events in declining forests (Beier et al, 2008;Comeau et al, 2019Comeau et al, , 2021. However, this study is the first to detect this response in an apparently healthy oldgrowth forest, in which no trees showed visual signs of decline, such as discolored foliage and thinning crowns.…”
Section: Relations With Winter Conditions Are An Early Warning Of Yellow-cedar Declinesupporting
confidence: 91%
See 2 more Smart Citations
“…The sensitivity of yellow-cedar to warm dry winters in recent decades is consistent with other studies showing increased vulnerability to late-winter thaw-freeze events in declining forests (Beier et al, 2008;Comeau et al, 2019Comeau et al, , 2021. However, this study is the first to detect this response in an apparently healthy oldgrowth forest, in which no trees showed visual signs of decline, such as discolored foliage and thinning crowns.…”
Section: Relations With Winter Conditions Are An Early Warning Of Yellow-cedar Declinesupporting
confidence: 91%
“…However, this study is the first to detect this response in an apparently healthy oldgrowth forest, in which no trees showed visual signs of decline, such as discolored foliage and thinning crowns. When comparing variation in individual ring-width indices from 1900 to 2015, we found some yellow-cedar suffered intermittent growth reductions after 1950 that may be consistent with thaw-freeze events and provide an additional early warning sign of decline (Cailleret et al, 2017;Comeau et al, 2021). We recommend careful monitoring of forest health to determine if canopy dieback or tree mortality of yellow-cedar results in future as winter climate continues to warm.…”
Section: Relations With Winter Conditions Are An Early Warning Of Yellow-cedar Declinementioning
confidence: 83%
See 1 more Smart Citation
“…In previous work within stands with visual evidence of yellow-cedar decline on Haida Gwaii, we have shown that yellow-cedars that have died or are visually declining grow alongside those with healthy crowns (Comeau et al 2019(Comeau et al , 2021. However, there are discrepancies between internal tree-ring and external crown symptoms in many trees (Comeau et al 2021). Yellow-cedars exhibit both positive and negative responses to climatic variation and change (Comeau et al 2019(Comeau et al , 2021.…”
Section: Introductionmentioning
confidence: 81%
“…On the island archipelago of Haida Gwaii, located 70 km west of the mainland, yellowcedar decline was unexpected due to the moderating effect of the Pacific Ocean yielding an ephemeral snowpack, but mild winter temperatures and few frosts (Banner et al 2014). However, many stands of yellow-cedar on Haida Gwaii now exhibit moderate-to highseverity decline, in which an average of 70% of trees are dying or dead (Comeau et al 2021). Given the relatively mild climate on Haida Gwaii, we hypothesize the mechanism driving yellow-cedar decline may differ from that characterized in forests on the mainland.…”
Section: Introductionmentioning
confidence: 89%